Longitudinal Assessment of Amyloid-β Deposition by [18F]-Flutemetamol PET Imaging Compared With [11C]-PIB Across the Spectrum of Alzheimer’s Disease - Hatashita, Shizuo; Wakebe, Daichi; Kikuchi, Yuki; Ichijo, Atsushi (Frontiers in Aging Neuroscience, 2019)
This study evaluates the longitudinal changes in the amyloid-β (Aβ) deposition with [18F]-flutemetamol (FMM) PET imaging across the spectrum of Alzheimer’s disease (AD), compared with [11C]-Pittsburgh Compound-B (PIB) PET. Eleven AD, 17 mild cognitive impairment (MCI) and 13 cognitively normal (CN) subjects underwent neuropsychological assessment and amyloid PET imaging using [18F]-FMM and [11C]-PIB during a follow-up period. Regions of interest were defined on co-registered MRI, and the FMM and PIB standardized uptake value ratio (SUVR) was used in the same cortical regions. The annual rate of change in FMM and PIB SUVRs was calculated. Cortical FMM SUVR in amyloid-positive subjects increased over a follow-up of 3.1 ± 0.5 years. An individual FMM SUVR was significantly correlated with PIB SUVR at baseline and at follow-up in the same AD, MCI, and CN subjects. The annual rate of increase in FMM SUVR was significantly greater in typical amyloid-positive (0.033 ± 0.023, n = 7), focal positive MCI (0.076 ± 0.034, n = 4) and positive CN (0.039 ± 0.027, n = 4) while that in AD (0.020 ± 0.018, n = 11) was smaller. Among amyloid-positive patients, the baseline FMM SUVR was inversely related with the increased rate in FMM SUVR (r=−0.44, n = 26, p < 0.05). An individual annual rate in change of cortical FMM SUVR was significantly correlated with that in cortical PIB SUVR. Our results suggest that the [18F]-FMM PET imaging can clarify the longitudinal assessment of Aβ deposition across the AD spectrum, similarly to [11C]-PIB PET. The Increase in Aβ deposition is faster in the predementia stage but not at a constant rate across the clinical stages of the AD spectrum.